Growth strategies and value creation: what works best for stock exchanges? - Iftekhar Hasan; Heiko Schmiedel; Liang Song (Bank of Finland, 2010)
In recent years, demutualized stock exchanges have increasingly engaged in M&A and alliance activities. To shed light on this topic, we investigate short-run share price responses to the formation of 110 stock exchange M&As and alliances in the period 2000 2008. Our ?ndings show that the average stock-price responses to a stock-exchange M&A or alliance is positive. Stock exchange M&As create more value than alliances. For alliances, joint ventures generate more value than non-equity alliances. More value is created when the integration is horizontal and cross-border than when it is vertical and domestic. Evidence is also found for learning-by-doing effects in stock exchange integration activities. Finally, we find that the better the shareholder protection, accounting standards and degree of capital market development in the partnering exchange s country, the higher the merger and alliance premium. These patterns also obtain when we examine long-run performance measures such as the three-year buy-and-hold abnormal return, change in ROA (ROE), change in liquidity, and change in market capitalization of IPO between years t-2 and t+2.
URN:NBN:fi:bof-20140807339
Keywords: 330